Mitigasi Dampak Kekerasan terhadap Perempuan dan Anak di Distrik Sorong Kepulauan Kota Sorong - Ali, Muhammad; Rais, Lukman; Gafur, Muzna A. A; Ponisri; Sukmawati; Rosalina, Febrianti; Riskawati (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2023)
This research aims to analyze the impact of violence against women and children, as well as mitigation and prevention efforts. The study employs a mixed methods approach that combines qualitative and quantitative methods. Data collection methods include observation, questionnaires, and in-depth interviews, with data analysis conducted both qualitatively and quantitatively. The research findings indicate that the impact of violence against women encompasses both physical and non-physical injuries that affect the psychological well-being of the women involved. This can lead to long-term trauma, depression, and the potential for these women to perpetrate violence against others, including children. The study also reveals significant impacts of violence against children, including psychological disturbances and mental effects that can hinder their ability to interact socially. Children who are victims of violence tend to experience deep trauma, exhibit aggressive behavior, and struggle to adapt to their social environment. In efforts to mitigate and prevent violence against women and children, there is a need to enhance family functioning and intensify awareness and education campaigns by the government and relevant institutions, such as the police and community organizations. Synergy between the community and the government is key to the success of these mitigation efforts, enabling the effective prevention of violence against women and children through the institutionalization of preventive actions.